Dampak sosial ekonomi dan implementasi nilai-nilai Pancasila oleh kelompok tani - Kamilatil Abdi; Fatmariza Fatmariza; Maria Montessori; Hasrul Hasrul (Journal of Education, Cultural and Politics, 2026)
This study aims to identify the social and economic impacts of women's involvement in the Tunas Muda farmer group and to identify the implementation of the Pancasila values ​​of the third principle by women in the Tunas Muda farmer group in Sungai Manau Village. This study uses a qualitative approach with descriptive methods. The selection of informants in this study through purposive sampling consisting of village officials, agricultural extension workers, members of farmer groups, and local communities, through data collection techniques in the form of observation, interviews and documentation studies. The validity test of this research data uses source triangulation and method triangulation techniques. Data were analyzed using the Miles and Hamberman model through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the involvement of women in the Tunas Muda farmer group has a social impact in the form of increased relationships between members and increased knowledge. Meanwhile, the economic impact felt is the ease of access to loans for farmer group members and helps meet family economic needs. In addition, the implementation of the Pancasila values ​​of the third principle is seen in the practice of mutual cooperation in agricultural activities that illustrates a sense of togetherness among members, and decision making through deliberation. Thus, the Tunas Muda Farmers Group not only improves social and economic welfare, but also strengthens the values ​​of unity, togetherness, and participation in community life, thereby supporting the success of the women's empowerment process in a sustainable manner.